2020
DOI: 10.1098/rstb.2019.0615
|View full text |Cite
|
Sign up to set email alerts
|

Costs of reproduction and ageing in the human female

Abstract: Evolutionary theories of ageing point to reproduction as a significant factor to consider when asking why ageing occurs and why there is inter-individual variation in its progression. Reproduction in human females is costly, in terms of energy, nutrients and metabolic adjustments. Thus, it is expected that women who experienced high reproductive effort resulting from multiple reproductive events will age faster. However, the evidence for long-term negative effects of reproduction is not conclusive. The lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 78 publications
(87 reference statements)
1
29
0
Order By: Relevance
“…Overall, these findings suggest that women's reproductive history should be considered as an important factor influencing post-reproductive health and aging. Of course, there are other traits related to women's reproductive history that could explain variations in health status among older women (for review, see: Jasienska, 2009Jasienska, , 2020. Even the relationship between the number of sons and inflammaging could potentially be influenced by the timing of reproduction (very early or very late reproduction may be more risky for mothers [Laopaiboon et al, 2014;Tomassini et al, 2018]), birth sequence (sons born in succession or as twins could be more challenging for the maternal organism [Grundy & Tomassini, 2005;Jelenkovic et al, 2014]) or length of interbirth intervals (shorter intervals result in less time for maternal maintenance and repair [Ellison, 2001;Mace & Sear, 1997;Schummers et al, 2018]).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings suggest that women's reproductive history should be considered as an important factor influencing post-reproductive health and aging. Of course, there are other traits related to women's reproductive history that could explain variations in health status among older women (for review, see: Jasienska, 2009Jasienska, , 2020. Even the relationship between the number of sons and inflammaging could potentially be influenced by the timing of reproduction (very early or very late reproduction may be more risky for mothers [Laopaiboon et al, 2014;Tomassini et al, 2018]), birth sequence (sons born in succession or as twins could be more challenging for the maternal organism [Grundy & Tomassini, 2005;Jelenkovic et al, 2014]) or length of interbirth intervals (shorter intervals result in less time for maternal maintenance and repair [Ellison, 2001;Mace & Sear, 1997;Schummers et al, 2018]).…”
Section: Discussionmentioning
confidence: 99%
“…reliance on hunted versus other foods). Fertility patterns are not explicitly considered in the present study, but they can influence both somatic condition, particularly for women ( Jasienska, 2020 ; Ryan et al, 2018 ; Stieglitz et al, 2015a ; Stieglitz et al, 2019 ; Ziomkiewicz et al, 2016 ), and economic productivity ( Hooper et al, 2015 ; Kramer, 2005 ). Extensive longevity may be a novel life history feature of modern H. sapiens that was absent among prior hominin species; extant hunter-gatherers with relatively minimal acculturation exhibit a modal adult lifespan of 68–78 years ( Gurven and Kaplan, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Is this the biological reality or a product of methodological limitations? In this volume, Jasienska [104] advocates for evolutionarily informed approaches to design more powerful studies of the health effects of reproduction, including more realistic assessments of reproductive effort. However, using detailed measures of reproductive effort, Phillips et al [92] found that wild chimpanzee females experienced only transient increases in faecal parasites during pregnancy, and high fertility predicted lower, not higher parasitism with age.…”
Section: (D) Sex Differences In Ageingmentioning
confidence: 99%
“…Is this the biological reality or a product of methodological limitations? In this volume, Jasienska [104] advocates for evolutionarily informed approaches to design more powerful studies of the health effects of reproduction, including more realistic assessments of reproductive effort. However, using detailed measures of reproductive effort, Phillips et al .…”
Section: Key Themes From This Volumementioning
confidence: 99%